Methodological proposal for the standardization of the Electronic Navigational Chart scheme in the Caribbean Sea - Bonfante, Olga; Torres Parra, Rafael Ricardo; Castillo, Julio (The International Hydrographic Review, 2025)
Since the approval of the use of Electronic Navigational Charts (ENC) as equivalent to paper nautical charts, hydrographic services worldwide began their production following existing cartographic schemes. This paper proposes to standardize ENC production schemes at the regional scale through a regular grid system, which unifies the scale of compilation and cell size by navigational purpose. The implementation of this system requires defining the origin of the grid and facilitates the nomenclature of the ENCs. Additionally, this standardization would help for the harmonized production of ENCs by improving their coverage. The proposed methodology is used to formulate an ENCs scheme in the Caribbean Sea, which is part of the Meso American & Caribbean Sea Regional Hydrographic Commission, in order to show its application and advantages. For this region it is proposed to generate a regular grid scheme with cell sizes and compilation scales (1:K) for Overview, General and Coastal navigational purposes of 24° × 24°, 6° × 6° and 1.5° × 1.5° and 1:3,000, 1:700 and 1:180 respectively, which allows to eliminate irregularities between the ENCs. This proposal contributes to the safety of maritime activities, seeking to enhance the quality of the ENC products in this region and increase trust to Electronic Chart Display and Information System users through enhanced visualization and seamless transition between ENCs of the same compilation scale. Additional serves as input for the modernization of the ENC schemes in the different Regional Hydrographic Commissions of the International Hydrographic Organization.